The use of economic instruments of land management to conserve biological diversity: international experience - Demydenko, L. (Land Management, Cadastre and Land Monitoring, 2017)
Studied international experience of using economic instruments to stimulate land users to preserve biodiversity. Keywords: economic instruments, incentives, biodiversity, protected areas.